POLA INTERAKSI GURU DAN SISWA MODEL LASWELL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 2 MANDIRAJA BANJARNEGARA - Aflah Kusumawarzaki, Rizqon; Mayasari, Novi (Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the application of the Laswell model of teacher and student interaction patterns in Islamic Religious Education and Character Education learning at SMP Negeri 2 Mandiraja and to analyze the weaknesses and strengths of the Laswell model of teacher and student interaction in Islamic Religious Education and Character Education learning at SMP Negeri 2 Mandiraja. This study uses a descriptive qualitative field research method. The application of the Laswell model of teacher and student interaction patterns in Islamic Religious Education and Character Education learning at SMP Negeri 2 Mandiraja includes one-way interactions that are applied through lecture activities, namely to explain Islamic Religious Education and Character Education material with an interesting style and intonation, two-way interaction patterns through questions and answers to determine the extent of mastery of the subject matter, three-way interaction patterns, namely through group discussion activities to determine students' critical thinking skills in delivering Islamic Religious Education material and answering students' questions. The multi-way or all-way interaction pattern is carried out by the teacher through lecture activities, questions and answers and discussions on the material that has been delivered and continued by answering questions in the book given by the teacher to students to measure the ability to answer correctly.